The IDENTIFICATION OF COMFORT SPACE ON INDONESIA’S MINISTRY OF RELIGIOUS OFFICE DESIGN’S - Fayazid, M Syauqi Hikam; Idham, Noor Cholis (Border: Jurnal Arsitektur, 2025)
This study aims to identify the comfort space in the Design of the Indonesian Ministry of Religious Office of the Regency/City for users. The method used is critical analysis based on architectural documents to explore on applicating of the comfort space principle in office design. This study uses architectural design documents of the Indonesia’s Ministry of Religious Office and precedent studies during the design process as main data. The results show the design of the Indonesian Ministry of Religious Office adopt universal and inclusive design for guests, natural lighting, passive design (windows, rosters, and cross ventilation), flexible modular layout and synergistic workspace, connecting space with the surrounding environment, and adapts to tropical climate in Indonesia. However, there are limitations to assistive devices for people with visual disabilities and need privacy settings on opening windows. This study recommends improvisation of the design for selected architects, quality control checks during the planning process to construction, and post-occupancy evaluation (POE) to ensure user rights and comfort.